MPI/OpenMP Hybrid Parallel Algorithm of Resolution of Identity Second-Order Møller-Plesset Perturbation Calculation for Massively Parallel Multicore Supercomputers - Katouda, Michio; Nakajima, Takahito (Journal of chemical theory and computation, 2013)
A new algorithm for massively parallel calculations of electron correlation energy of large molecules based on the resolution of identity second-order Møller-Plesset perturbation (RI-MP2) technique is developed and implemented into the quantum chemistry software NTChem. In this algorithm, a Message Passing Interface (MPI) and Open Multi-Processing (OpenMP) hybrid parallel programming model is applied to attain efficient parallel performance on massively parallel supercomputers. An in-core storage scheme of intermediate data of three-center electron repulsion integrals utilizing the distributed memory is developed to eliminate input/output (I/O) overhead. The parallel performance of the algorithm is tested on massively parallel supercomputers such as the K computer (using up to 45 992 central processing unit (CPU) cores) and a commodity Intel Xeon cluster (using up to 8192 CPU cores). The parallel RI-MP2/cc-pVTZ calculation of two-layer nanographene sheets (C150H30)2 (number of atomic orbitals is 9640) is performed using 8991 node and 71 288 CPU cores of the K computer.